Characteristic clinical signs and blood parameters in cats with Feline Infectious Peritonitis - Moyadee, Wassamon; Jaroensong, Tassanee; Roytrakul, Sittiruk; Boonkaewwan, Chaiwat; Rattanasrisomporn, Jatuporn (Agriculture and Natural Resources, 2019)
Feline infectious peritonitis (FIP) is a common disease with high mortality rates in cats that occurs as either an effusive or non-effusive form. Confirmation of FIP in clinical practice is difficult and remains a challenge because there are no pathognomonic lesions or specific diagnostic indicators. Thus, clinical features were investigated to evaluate the hematological and biochemical parameters between FIP and non-FIP cats. A sample of 50 blood donor cats and 50 effusive FIP cats presented at the Kasetsart University Veterinary Teaching Hospital were divided into non-FIP and FIP groups, respectively. The average age of FIP cats was significantly (p < 0.05) lower than for non-FIP cats. The results indicated that cat breeds correlated with FIP (p < 0.05). Significant results concerning hematological and biochemical findings revealed values of packed cell volume (PCV), red blood cells (RBC), hemoglobin (HGB), mean corpuscular volume (MCV), lymphocytes, eosinophils, blood urea nitrogen (BUN), creatinine, alanine aminotransferase (ALT), albumin and albumin:globulin (A:G) ratio in the FIP group were lower and numbers of white blood cells (WBC), segmented neutrophils, plasma protein (PP), total protein and globulin in the FIP group were higher than in the non-FIP group (p < 0.05). In conclusion, anemia, neutrophilia, lymphopenia, hypoalbuminemia, hyperglobulinemia and a low A:G ratio presented as hematological and biochemical changes in FIP cats. Blood profiling could be a useful approach for FIP diagnosis to assist clinicians to determine and evaluate the correct treatment, prognosis and progressive monitoring.